تحديات البحث العلمي في ظل العولمة - علي مكطوف, كرار (Journal of College of Education, 2019)
The phenomenon of Globalization seems unclear in its features , aims and trends because the circles of this phenomenon are not complete yet , but we look at it through its features and the most prominent feature is that of economical globalization which is regarded as the real essence for the development of capitalism system throug the period after imperialism which is called various is globalization or astral . but the term of Globalization spread in the world and it means the development which accompanied the capitalism system from the beginning that means from the time of merchants until the period after imperialism This development is accompanied and invaded by the scientific and technological development which provided the production means with different educational methods that appeared at the scientific research , for that they regarded the scientific research as the basic source that invades the educational development after that time . This thing led to a great improvement in the means of production and in different services the improvement in the hand made means of production is followed by improvement in the commercial means of production , and that is followed by improvement in the means of electrical productions then into the means of nuclear production which is called as the third technological and scientific revolution . The circles of this revolution are not complete yet because that the used production means spread for  a little rate comparing with the means of electrical production . Though the stages of the development in science and technological system from the industrial revolution till this time focuses on the discovery and the use of different means of energy that became very important and needed as substitute sources especially after the second world war this thing motivate the developed countries to alert the means of scientific research and the educational development and directing this to create alternatives with low, costs from energy especially from petrol . Because of that , the scientific research became the base which is applied to develop the different educational circles . The economical Globalization came as a result of the improvement of the system of ( Science and technology ) and from this , this scientific research gains its important as a basic  way to restrict the phenomenon of economical Globalization which may be become an effective mean to face this phenomenon especially is that some arabic countries differ from other countries in that they are the source of cheap energy . So by this the scientific research and the educational development become very important and essential not only for firiding substitutes of energy but also as a mean to face the political